Bacterial cellulose nanofibers improved the emulsifying capacity of soy protein isolate as a stabilizer for pickering high internal-phase emulsions. (March 2021) - Liu, Zhe; Lin, Dehui; Shen, Rui; Yang, Xingbin
Abstract: In this work, we report for the first time the use of bacterial cellulose nanofibers/soy protein isolate (BCNs/SPI) composite colloidal particles as nature materials to be an effective particle stabilizer for the development of high internal phase emulsion (HIPE, oil-in-water) with 75% oil phase. The composite colloidal particles were prepared by an antisolvent approach, and the characterizations of the prepared composite colloidal particles with different BCNs/SPI ratios (1:25, 3:25, 5:25, 7:25 and 9:25 w/w) were investigated in the present work. FTIR analysis showed that BCNs/SPI colloidal particles were formed mainly through hydrogen bonds. The rheological property, crystallinity, thermal stability, and wettability of BCNs/SPI colloidal particles were improved as compared with pure SPI. Furthermore, the stability of HIPEs increased with the increase of BCNs/SPI ratios, where HIPEs stabilized by BCNs/SPI composite colloid particles with a ratio of 7:25 showed the highest stability during a 2-month storage period. Therefore, this study suggested that BCNs significantly improved the emulsifying capacity of SPI and the prepared BCNs/SPI composite colloids particles have great potential applications in the food industry. Graphical abstract: Image 1 Highlights: The properties of BCNs/SPI colloidal particles were improved as compared with SPI. BCNs/SPI colloidal particles formed a gel-like network at the oil-water interface. BCNs improved the emulsifying capacity of SPI as a stabilizer for HIPEs. BCNs/SPI colloidal particles show a great potential of application in food industry.